Optimasi Produksi Asap Cair Dari Kayu Medang (Cinnamomum sp.) Menggunakan Metode Permukaan Respon - H. A. Oramahi; Farah Diba; Rizka Diah Permana (Universitas Lambung Mangkurat, 2020)
In this work medang wood (Cinnamomum spp.) was pyrolyzed to produces wood vinegar. The effect of several parameters including the wood particle size, pyrolysis temperature, and pyrolysis time on the pyrolysis efficiency was tested to identify the optimal wood vinegar production conditions. The efficient response surface methodology (RSM) with the Box-Behnken design (BBD) was used for modeling and optimization of the process parameters. RSM used three variable designs namely particle size of wood of 2.38, 3.36, and 4.76 mm, respectively, pyrolysis temperature of 370, 400 and 430°C, respectively, and pyrolysis times 90, 120 and 150 minutes, respectively, with the total of 15 experimental runs. The responses of the BBD fitted with a second-order polynomial equation, illustrating the wood vinegar yield was Y = 15.20 + 0.31 X1 + 5.00 X2 + 0.48 X3 – 1.84 X12 – 1.18 X22 + 0.63 X1.X2 + 0.35 X1.X3 + 0.31 X2.X3 – 0.27 X3.X3. The optimal conditions found to be at the particle size of wood, pyrolysis temperature, and pyrolysis time were 4.76 mm, 475 °C, 195 minutes, respectively, and yield of wood vinegar was 22.90%.